ENTREPRENEURSHIP: SYSTEMATIC REVIEW OF STUDIES APPROVED IN ADMPG ANNALS (ADMPG Journal, 2020)
The entrepreneurship received substantial attention from researchers because of its importance as driver of economic development. The journals like, Entrepreneurship Theory and Practice, International Entrepreneurship and Management Journal, Strategic Entrepreneurship Journal, emerged exclusively to discuss this subject, being considered as relevant journals in the academy. Following this premise, this study aims to review the articles selected for the annals of the International Congress of Administration - ADMPG, from 2004 to 2018. We make a systematic bibliographical review. 149 productions were analyzed with entrepreneurship as subject. As a result of the review, we conclude that the years 2014, 2015, 2016 and 2017 were highlighted with the largest number of papers selected, since in 2014, the congress received a specific thematic area to papers on the theme. There is a balance in the articles approach, where 49.64% analyzed journals focus on the organizational level and 53.96% at the individual level. We found four major frameworks of the analyzed studies: (i) Individual entrepreneurial characteristics; (ii) Organizational entrepreneurial characteristics (iii) Entrepreneur training (iv) Incentive to entrepreneurship. It is noticed that the last two frameworks are still subject to discussion at the congress in question, since they received less attention until the year 2018. Thus, as suggestions for future research, it is believed that a better entrepreneurship in order to enable the evolution of the field with the development of future research.